Impact of mindfulness for people with arthritis: IJPDS (2017) Issue 1, Vol 1:043, Proceedings of the IPDLN Conference (August 2016) - Brophy, Sinead; Cooksey, Roxanne; Kennedy, Jonathan; Davies, Helen (International Journal of Population Data Science, 2017)
ABSTRACT Objective To examine the impact of mindfulness-based stress reduction (MBSR) for people with ankylosing spondylitis (AS). Methods 193 People with AS were invited to take part in an MBSR 8 week course. The data linkage component of this study examined number of visits to the general practitioner before and after the course in participants and non-participants of the course (500 people taking part in a cohort study but not invited to the course). Results Of 193 people invited, 43 (22%) consented and took part in the course, GP records were available for 41 (95%) of MBSR participants and 457 (91%) of the 500 comparison group. There was a mean of 7.6 (median 3) visits to the GP in the 12 month period before the course for those undertaking MBSR and 4.6 (median 0) visits in the 12 month period after the course. This compared with 5.5 (median 0) visits (12 months before a random date) and 4.1 (median 0) visits (12 months after a random date) in the comparison group. Using Wilcoxon rank-sum (Mann-Whitney) test showed a significant reduction in GP visits in the MBSR group after the course compared to the comparison group. Conclusions Those who chose to attend an MBSR course had a higher number of visits to the GP before attending the course, than the comparison group. However, after attending the stress reduction course the number of visits to the GP reduced to levels equivalent to the comparison group. This study suggests that mindfulness based stress reduction could be effective in reducing the number of visits to the GP for people with arthritis who regularly see their GP. The findings from this study suggest a full RCT and cost effectiveness analysis is warranted.